Design and delivery of messenger RNA-based vaccines. (13th August 2021) - Pichon, Chantal; Perche, Federico
Abstract : In these last years, we are witnessing the emergence of a new class of biopharmaceuticals based on messenger RNA (mRNA). One of the most promising applications of mRNA is its use as vaccines. Many reports, including ours, have demonstrated the preclinical efficacy of mRNA vaccines. mRNA vaccines have several advantages over traditional vaccines or even DNA vaccines. Unlike attenuated or inactivated vaccines, mRNA encodes for a specific antigen that will be expressed in situ and stimulates both the innate immune system and an adaptive immunity to promote both humoral and cellular immune responses.